COVID-19 breakthrough infections during the circulation of Delta and Omicron variants in Tirana, Albania, April 2021–March 2022 - Fiona Konomi; Silvia Bino; Kujtim Mersini; Arlinda Ramaj; Kostas Danis (PLoS ONE, 2025)
Background COVID-19 breakthrough cases raised crucial questions about vaccine effectiveness, implications for public health, and the dynamics of viral transmission. We described vaccine breakthrough infections in Tirana during the Delta (01/07/2021-12/15/2021) and Omicron (16/12/2021–31/03/2022) periods, to better inform mitigation and vaccination strategies. Methods We extracted data from 01/04/2021–31/03/2022 (study period) from two systems: the Albanian infectious disease surveillance system, and the national vaccination database. We defined a COVID-19 case as a resident of Tirana who tested (RT-PCR/antigen) positive for SARS-CoV-2 on a respiratory specimen. We defined vaccine breakthrough infection as having a COVID-19 positive specimen collected ≥14 days after the primary series of vaccines (2 doses). We calculated risk of breakthrough infection using the total number of fully vaccinated individuals as denominator and risk ratios (RR) using binomial regression. Results During the study period, 23,875 cases were reported in Tirana; 36% (291,445/800,000) individuals were fully vaccinated and among those, 9,156 (3.1%) breakthrough infections were detected. The median time from vaccination to breakthrough infection was 149 (IQR:102–209) days. The risk of breakthrough infection was higher in 0–39-year-olds (RR = 3.01;95%CI = 2.78–3.27) and during the Omicron period (RR = 32; 95%CI = 30.00–34.91). Those receiving Gam-COVID ((RR = 1.64;95%CI = 1.39–2.02), ChAdOx1-S/Vaxzervria (RR = 1.56;95%CI = 1.48–1.65), or BNT162b2-Comirnaty (RR = 1.36;95%CI = 1.31–1.41) had a higher risk of breakthrough infection compared with those vaccinated with CoronaVac. Conclusions Incidence of COVID-19 breakthrough infection was significantly higher during the Omicron period and among younger individuals in Tirana. The substantially elevated risk associated with Omicron variant breakthrough infection and the decline in infection protection after a 5-month period, warrants close monitoring and rapid adaptation of vaccination strategies, including promoting booster vaccination to reduce breakthrough infections in the future.